Upaya Guru Pendidikan Agama Islam dalam Meningkatkan Ketahanan Moral Generasi Z Terhadap Dampak Media Sosial di SDN 1 Kalimendong - Nani Fatchatul Chabibah; Sri Haryanto; Darul Muntaha (Islah Tarbawi: Journal of Islamic Education and Learning, 2026)
This study was inspired by the growing presence of social media among elementary school children, which has an impact on the ethical growth of Generation Z. While social media offers benefits like easier access to information, it also carries drawbacks such as a decrease in politeness, poor discipline, and behavioral changes in students. In this context, teachers of Islamic Religious Education have a crucial role in fostering and enhancing the moral strength of students so they can confront the adverse effects of social media. The purpose of this study is to: (1) assess the moral resilience of Generation Z students regarding the effects of social media at SDN 1 Kalimendong, (2) recognize the different ways social media influences students' moral values, and (3) evaluate how Islamic Religious Education teachers are working to enhance the moral resilience of Generation Z against social media's effects at SDN 1 Kalimendong. This research adopted a qualitative descriptive method with a field research framework. Data were gathered through interviews, observations, and document analysis. The participants of the study included the principal, teachers of Islamic Religious Education, classroom educators, fifth and sixth-grade students, and parents. The analysis of data involved reducing data, presenting data, and drawing conclusions, with the reliability of the data being checked through both source triangulation and technique triangulation. Findings from the research show that the moral resilience of Generation Z students at SDN 1 Kalimendong is generally strong, though certain students are still affected by excessive use of social media. Social media can positively contribute to expanding students’ knowledge and awareness; however, it can also negatively influence their behavior, communication etiquette, discipline, and socialization. The actions taken by Islamic Religious Education teachers to bolster students' moral resilience include promoting religious practices, serving as role models, providing guidance and counseling, monitoring the use of social media, collaborating with parents, and incorporating Islamic ethical values into their teaching. These initiatives are found to be effective in encouraging students to adopt selective, disciplined, and responsible behaviors in their use of social media.